2011
DOI: 10.1103/physrevlett.107.235301
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Topological Order in Time-of-Flight Measurements

Abstract: In this Letter, we provide a general methodology to directly measure topological order in cold atom systems. As an application, we propose the realization of a characteristic topological model, introduced by Haldane, using optical lattices loaded with fermionic atoms in two internal states. We demonstrate that time-of-flight measurements directly reveal the topological order of the system in the form of momentumspace Skyrmions. DOI: 10.1103/PhysRevLett.107.235301 PACS numbers: 67.85.Àd, 03.65.Vf Different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
307
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(312 citation statements)
references
References 34 publications
(48 reference statements)
2
307
0
Order By: Relevance
“…Besides detecting edge properties, the bulk Chern number can also be used to demonstrate the topological nature of our proposed chiral p-wave superfluidity. For the detection of Chern numbers, one may adopt the existing proposals either from time-of-flight measurement [40][41][42][43] or from Bloch oscillation technique 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides detecting edge properties, the bulk Chern number can also be used to demonstrate the topological nature of our proposed chiral p-wave superfluidity. For the detection of Chern numbers, one may adopt the existing proposals either from time-of-flight measurement [40][41][42][43] or from Bloch oscillation technique 44,45 .…”
Section: Resultsmentioning
confidence: 99%
“…Such a control has been recently used in an experimental implementation of honeycomb lattices for ultracold fermions [6]. Several schemes have been discussed in the literature [7,8] with the aim of engineering topologically non-trivial twodimensional systems on honeycomb lattices, which naturally reproduce well-known paradigmatic models such as the Haldane model [9]. The discussed setups rely on the laser implementation of tight-binding models on honeycombs having both nearest-neighbor and next-nearestneighbor hoppings: these hoppings simulate the presence of a staggered magnetic field which breaks time-reversal symmetry and opens band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in Ref. [7] it has been shown that time of flight measurements, resolved with respect to the different spin species, allow us to reconstruct the spin polarization of the lowest band in the first Brillouin zone. From this polarization one can calculate a spin winding number which, for the Chern insulators related to the Haldane model, directly provides the Chern number of the occupied band, and thus the number of protected edge states [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, a practical way is to modulate the atomic hopping parameters in a honeycomb OL by using the synthetic gauge poten- * Electronic address: slzhunju@163.com tials [14] or the laser-assisted tunneling (LAT) [15,16], following the schemes proposed in Refs. [17][18][19]. However, the LAT technique has not yet been demonstrated in honeycomb OLs, but in square optical (super) lattices [20][21][22].…”
mentioning
confidence: 99%